A Rapid And Sensitive Method For Estimation Of Bepotastine In Human Plasma By Lcms/Ms - MAMTA P. DEVADIGA; ANANDAN P; ARINDAM MUKHOPADHYAY (International Journal of Pharma and Bio Sciences, 2011)
Bepotastine is a new antihistamine drug for treatment of itchy and watery eyes as well as for allergic rhinitis and chronic urticaria. Bepotastine and cetirizine (IS), extracted from the plasma by SPE method, were separated on a Zorbax SB C18 column at 500C using the mobile phase mixture of methanol and ammonium formate (80:20, v/v) at a flow rate of 0.8 ml/min. The analytes were detected in API 3000 Mass spectrometer in the positive electrospray ionization mode (split ratio 4:1) with multiple reactions monitoring (MRM). The MRM transitions monitored were m/z for parent ion 389.1 & daughter ion 202.1 (bepotastine), m/z for parent ion 389.1 & daughter ion 201.2 (cetirizine). A linear calibration plot of bepotastine and I.S. was achieved in the concentration ranges of 0.505 to 538.713 ng/ml and the correlation coefficient was > 0.9995. Recoveries were consistently more than 71.71%. The assay was specific, precise, accurate and reproducible.